Peningkatan Pengetahuan, Sikap dan Perilaku Siswa SD sebagai Kader Cilik Pengawas Jajanan Anak Sekolah melalui Pelatihan - Oslida Martony (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the effectiveness of the training in improving the knowledge, attitudes, and behavior of elementary school students as a cadre of school hawker supervisors in Lubuk Pakam. The method in this study uses the action research method, using the student facilitator and explaining the training model. The results of the empowerment research with the student facilitator and teaching training model can improve the knowledge, attitudes, and actions of the young cadres, there are significant differences in the values of knowledge, attitudes and activities based on cycle I namely (p = 0.001, p = 0.001, and p = 0.001), and in the second cycle (p = 0.001, p = 0.001, and p = 0.001). In conclusion, the training carried out on Muhammadiyah elementary school students is useful as a cadre of child food supervisors of school snacks. Keywords: Snacks for School Children, Young Cadres, Knowledge, Behavior, Attitudes